Visualisasi Spasial Jalur Pendakian: Studi Kasus Di Gunung Muria - Saputra, Zidan Wahyu; Mukasyaf, Aziz Akbar (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Mount Muria, located in Kudus Regency, has immense natural potential as a destination for special-interest tourism, particularly hiking. However, its development and utilization remain suboptimal. One major challenge is the lack of structured and accessible information about hiking trails, making it difficult for visitors to plan their hikes. This study aims to analyze the characteristics of hiking trails on Mount Muria. The research focuses on the trails in Rahtawu Village, specifically Natas Angin Peak and Peak 29. Data were collected through field surveys involving direct observation, documentation (travel distance, time, slope, and facilities), and trekking (coordinates of checkpoints and facilities). The analysis employs a percentage descriptive method to evaluate hiking trail scores based on distance, slope, time, and facilities. Results show that the Natas Angin trail is 3,720 meters long with an average slope of 30.33%, leading to a longer travel time of approximately 204 minutes. In contrast, the Peak 29 trail is 5,004 meters long with a gentler slope of 15%, allowing for a shorter travel time of about 192 minutes. While shorter, the Natas Angin trail is more challenging, making it better suited for experienced hikers, whereas Peak 29 is more suitable for beginners. This study provides valuable information for hikers to plan their trips and emphasizes the importance of optimizing trail information to improve safety and comfort during hikes on Mount Muria.